2010
DOI: 10.1109/jsen.2009.2036050
|View full text |Cite
|
Sign up to set email alerts
|

Nanosensor and Breath Analyzer for Ammonia Detection in Exhaled Human Breath

Abstract: The detection and monitoring of gases in exhaled human breath up to date has been limited by the lack of appropriate materials and technologies which could rapidly and selectively identify the presence and monitor the concentration of trace levels of specific analytes-biomarkers. We present a metal oxide-based nanosensor that is highly specific to ammonia gas in breath-simulating environments at low part-per-billion concentrations. The design of a handheld breath analyzer for gas detection in exhaled human bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 13 publications
1
62
0
Order By: Relevance
“…Breath ammonia has been used to study the efficacy of haemodialysis in end stage renal failure. Several studies on the efficacy of haemodialysis have shown good correlations between BUN and breath ammonia (Gouma et al, 2010;Hibbard et al, 2013;Narasimhan et al, 2001;Neri et al, 2012).…”
Section: The Role Of the Kidneys In Nitrogen Metabolismmentioning
confidence: 97%
“…Breath ammonia has been used to study the efficacy of haemodialysis in end stage renal failure. Several studies on the efficacy of haemodialysis have shown good correlations between BUN and breath ammonia (Gouma et al, 2010;Hibbard et al, 2013;Narasimhan et al, 2001;Neri et al, 2012).…”
Section: The Role Of the Kidneys In Nitrogen Metabolismmentioning
confidence: 97%
“…Other interesting developments related to systemic biomarkers in exhaled breath are the attempts to directly assess gases associated with human morbidity, such as ammonia 9 and acetone, 10 with the latter being used also as a proxy for blood levels of glucose. The directly measured gases, which have been intensively investigated as biomarkers in lung morbidity, are nitric oxide (NO) and carbon monoxide.…”
Section: Directly Determined Components Of Exhaled Breathmentioning
confidence: 99%
“…A new tag for pervasive sensing applications consists of a custom integrated circuit, an antenna for radio frequency energy harvesting, and smart tags for monitoring human body movements and some common sleep disorders or body temperature that are suitable for the human body [65][66][67]. We can use a hand-hold detecting and analyzing our breath or put a piezoelectric membrane sensor in our body to measure the pulse [68,69]. In addition, biomedical sensors fabricated by high-performance materials or advanced technologies could be adopted to make smart clothes for personal health care [70,71].…”
Section: Portable or Wearable Propertymentioning
confidence: 99%